Research progress on classification and advanced multimodal imaging features of pigment epithelial detachment in age-related macular degeneration - HE Yi; SU Yongyue (Yanke Xuebao)
Pigment epithelial detachment (PED) is one of the common manifestations of age-related macular degeneration (AMD), posing a significant threat to the patients’ vision. With the rapid advancement of imaging technology, the visualization of PED structure and content has improved considerably. The diagnostic methods and classification systems of PED are also evolving, enabling researchers to further explore its pathogenesis and disease course. However, current PED classification systems are numerous, with overlapping concepts that may cause confusion. This article reviews existing relative literature on AMD-related PED, summarizing the classification systems, multimodal imaging features, and recent imaging advances. The objective of this article is to standardize the diagnosis and guide treatment of PED, to provide systematic reference to the future research, ultimately advancing both clinical and research efforts related to PED.